Targeting Minimum Heat Transfer Area for Heat Recovery on Total Sites - Boldyryev, S.; Varbanov, Petar Sabev; Nemet, Andreja; Kapustenko, P. O.; Klemeš, Jiří Jaromír (The Italian Association of Chemical Engineering, 2013)
This paper upgrades the Total Site integration methodology, when accounting for a trade-off between capital and heat recovery by selection of optimal temperature levels for intermediate utilities and therefore, decrease capital cost. Heat transfer area for recuperation in Total Site is a two-fold problem and it depends on the Sink Profile on one side and on the Source Profile on another. The resulting temperature of intermediate utility is a result of a trade-off since the heat transfer area on Source side is decreasing, when temperature of IM is decreasing, however increased on Sink side. In the opposite higher intermediate utility temperature leads to higher area on the Source side and lower on Sink side. The temperature of each intermediate utility may be varied between specified lower and upper bounds subject to serving the Sink and Source Profiles.